Twenty seven new species of Orthocentrus (Hymenoptera: Ichneumonidae; Orthocentrinae) with a key to the Neotropical species of the genus - Veijalainen, Anu; Broad, Gavin R.; Sääksjärvi, Ilari E. (Zootaxa, 2014)
We describe 27 new species of parasitoid wasps of the genus Orthocentrus (Ichneumonidae: Orthocentrinae) from the Neotropical region, where previously only one species of the genus (O. insularis Ashmead) was known, and provide a key to all described Orthocentrus species of the region. Based on previous studies and additional material that we have seen from the region, describing these species is only an initial attempt to document the Neotropical orthocentrine fauna.